1985
DOI: 10.1093/nar/13.20.7473
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of the T4 recombination gene,uvsX, and its comparison with that of therecAgene ofEscherichia coil

Abstract: We have determined the nucleotide sequence of the uvsX gene of bacteriophage T4 which is involved in DNA recombination and damage repair, and whose product catalyzes in vitro reactions related to recombination process in analogous manners to E. coli recA gene product. The coding region consisted of 1170 nucleotides directing the synthesis of a polypeptide of 390 amino acids in length with a calculated molecular weight of 43,760. Amino acid composition, the sequence of seven NH2-terminal amino acids and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 28 publications
1
24
1
1
Order By: Relevance
“…Some of the RecA͞Rad51-family proteins were demonstrated by electron microscopy to form conserved, righthanded, spiral filamentous structures either by themselves or around DNA that is either single-stranded or double-stranded (20,21), and to some extent to have conserved amino acid sequences within the core region. It is remarkable that UvsX is only slightly conserved in amino acid sequence (22), but is well conserved in its biochemical functions and three-dimensional structure (16,23,24). The three-dimensional structure of DNAfree RecA, as solved by x-ray crystallography, revealed a righthanded helical filament (25), which is consistent with that obtained by electron microscopy as described above.…”
Section: Homologous Recombinationsupporting
confidence: 83%
“…Some of the RecA͞Rad51-family proteins were demonstrated by electron microscopy to form conserved, righthanded, spiral filamentous structures either by themselves or around DNA that is either single-stranded or double-stranded (20,21), and to some extent to have conserved amino acid sequences within the core region. It is remarkable that UvsX is only slightly conserved in amino acid sequence (22), but is well conserved in its biochemical functions and three-dimensional structure (16,23,24). The three-dimensional structure of DNAfree RecA, as solved by x-ray crystallography, revealed a righthanded helical filament (25), which is consistent with that obtained by electron microscopy as described above.…”
Section: Homologous Recombinationsupporting
confidence: 83%
“…Both ADP-AlF 4 Ϫ and ATP-␥-S are being used in this case as analogs for ATP, but it can clearly be seen that the filament structure depends on which analog is being used. Numerous studies have shown that aluminum fluoride can serve as a very good non-hydrolyzable analog for ATP (28), whereas it has been shown that ATP-␥-S is slowly hydrolyzed by proteins such as RecA (29)(30)(31). The smaller pitch filaments, resembling the ''collapsed'' state of the RecA filament formed in the absence of ATP (25), have previously been seen with hRad51 protein on ssDNA when ATP-␥-S was used as a cofactor (23).…”
Section: N-terminal Domain Of Rad51mentioning
confidence: 99%
“…The amplified DNA fragment was digested with EcoRI and cloned downstream of a λ phage promoter, P L , in the plasmid pNT45 (Fujisawa et al, 1985) to construct pGE615. pETN expressing RnlA was constructed as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Purification of Dmd MH1 cells were co-transformed with pGE615 and pNT204 (Fujisawa et al, 1985), the latter of which encodes a temperature-sensitive λ CI repressor. Transformed cells were incubated at 30°C to a density of 2 × 10 8 cells/ml in 500 ml LB medium, and the culture was shifted to 42°C for 2 hr to induce Dmd protein.…”
Section: Preparation Of Cell Extract For Rna Cleavage Assaymentioning
confidence: 99%